The Mediating Role of Social Media Engagement in the Relationship Between Social Media Advertising and Brand Awareness: Evidence from Luxury Resorts in Bali - Luh Linna Sagitarini; Made Suardani (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Social media has become a dominant channel for brand building in the hospitality sector, especially for luxury hotels, where visual storytelling and symbolic value are crucial. However, limited research has explored how paid social media advertising (SMA) influences brand awareness (BA) through consumer engagement. Objective: This study examines the direct and indirect effects of SMA on BA by applying the Stimulus–Organism–Response (SOR) framework, with social media engagement (ENG) serving as a mediator. Methods: A survey was conducted involving 250 domestic and international tourists who had engaged with paid campaigns on Instagram, Facebook, TikTok, and YouTube from five five-star resorts in Bali. The EPIC model—Empathy, Persuasion, Impact, and Communication—was used to assess advertising effectiveness, while regression analysis was employed to test the hypothesized relationships. Results: The results indicate that SMA directly enhances BA (β = 0.52, p < .001) and has an indirect effect through ENG as a significant mediator (β = 0.47 → β = 0.38, p < .001). ENG independently strengthens BA (β = 0.38, p < .001), and the model collectively explains 61% of the variance in brand awareness. This study contributes theoretically by integrating the EPIC model into the SOR framework and demonstrating that social media engagement functions as a key mediating mechanism between advertising stimuli and brand awareness outcomes. Conclusion: Practically, luxury hotel managers should invest in clear, persuasive, and emotionally resonant social media campaigns that stimulate consumer engagement, thereby reinforcing brand recognition and salience in competitive digital markets.